PROTOTIPE ALAT BANTU DETEKSI POLA WARNA UNTUK PENDERITA BUTA WARNA - Supriadi Syam; Nur Mustika (JTRISTE, 2018)
Research conducted aiming to create a prototype color pattern recognition tools for sufferers of color blindness. The sensor used is TCS3200-DB associated with the Arduino Uno. Closest Pair algorithm is embedded into micro controller using the Arduino IDE. The resulting output in the form of a color pattern that is represented by the letters that became the initials color sensor reading of the results have been processed with the Closest Pair Algorithm. The results obtained from this research TCS3200DB success rate and Closest Pair Algorithm in recognizing color result is 50%.